PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN REPUTASI KAP TERHADAP AUDIT DELAY - Diana, Novita Levi; Hariyanto, Eko; Setyadi, Edi Joko; Kusbandiyah, Ani (Jurnal Ekonomika dan Manajemen, 2024)
The study aims to determine the impact of profitability, solvency, corporate size and KAP reputation on audit delays in companies included in the Jakarta Islamic Index (JII) 30 Indonesia Stock Exchange in 2018–2022. Sixty samples were drawn from twelve firms that were listed on the Indonesia Stock Exchange's Jakarta Islamic Index 30 during the 2018–2022 research period. This study uses a quantitative methodology using secondary data from the Consolidated Financial Report of the business. The test results show that the solvency variable as measured by DER has a negative and significant effect on audit delay, and company size as measured by total assets Ln has a positive and significant effect on audit delay, while profitability as measured by ROA and KAP reputation as measured by dummy variables does not influence on audit delay